Analisis Produktivitas dan Pemasaran Komoditi Salak di Desa Sindang Kasih Kecamatan Ranomeeto Barat Kabupaten Konawe Selatan - Deden Darmanto; Lukman Yunus; Munirwan Zani (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2025)
This research aims: (1). To determine the productivity of snake fruit farming in Sindang Kasih Village, (2). Knowing the margin, costs and marketing channels for snake fruit in Sindang Kasih Village, and (3). Knowing the marketing efficiency of snake fruit farming in Sindang Kasih Village. The analysis in this research is analysis and uses primary data and secondary data. Determining the population in this research uses the census sampling method, while in marketing institutions the Snowball Sampling method is used. The results of this research show (1). The total productivity of salak farmers is 5,533 Kg/Ha/Year with an average of 2,160 Kg/Ha/Year in one harvest season. (2). There are 3 salak marketing channels in Sindang Kasih Village, namely Channel I: (Farmers - Consumers) direct channel, Channel II: (Farmers - Collectors - Retailers - Consumers) indirect channel, and Channel III (Farmers - Retailers). - Consumer) indirect channels. Successive marketing margin, namely channel I, is IDR. 12,500/Kg, Channel II at the collector level has a margin of Rp. 2,000/Kg and at the retailer level it has a margin of Rp. 5,000/Kg, and for channel III margin, at the retailer level the margin is IDR. 13,000/Kg. (3). The results of the analysis of (Farmer's Share) from the three channels, respectively Channel I is 100%, channel II is 41.67% and channel III is 64%